(untitled) (Al-Academy, 2023)
The tagged search (The aesthetic images in Mohammed Thanoun graphic) four chapters, Chapter I was concerned the statement of the research problem, the research importance and it’s needed, the goal of research in identifying the aesthetic images in the graphic of the artist’s, the research limits, and identifying the most important terms, chapter II came with theoretical framework and included three chapters: chapter I was interested in the aesthetic concept. chapter II is the image aesthetic in the graphic, and chapter III is the artist experience, Chapter III specializes in research procedures: community, sample, curriculum, tool, and sample analysis. Chapter IV ended with results, including: dynamic research sample illustrated of the diverse and changing movement and the artist’s ostracism and resentment from the rigid style. then the results included: He evokes the past in his artistic productions in structures of images aesthetic to remember his childhood by its social realism.